Religious pluralism and political stability obligations in agreement - Golemboski, David (New York, NY Routledge, 2023)
Introduction -- Part I. Stability and the foundations of political liberalism -- Justificatory stability -- Hobbesian political liberalism -- Motivating liberal loyalty -- Part II. Justificatory stability and the law of religion -- Conflicts of loyalty in religion and law -- Religious exemptions as a mechanism for political stability -- Endorsement, entanglement, and religious neutrality -- Conclusion.
Keywords: Political stability -- United States; Liberalism -- United States; Religious Pluralism -- Political aspects -- United States; Democracy -- Religious aspects -- United States; Freedom Of Religion -- United States; Electronic books; POLITICAL SCIENCE / Political Ideologies / Conservatism & Liberalism; RELIGION / Religion, Politics & State